(untitled) (Theatrum historiae, 2017)
This article analyses parts of the framework that determined the diplomatic mission of Count Philip Kinsky of Wchinitz and Tettau (1700–1749) in London from 1728 to 1736. In 1728, Emperor Charles VI decided to send Count Kinsky to the court of King George II of Great Britain to re-establish diplomatic relations. The aims of Kinsky’s mission to London were challenging, and his inexperience as well as the conflicting political aims of Charles VI and George II complicated matters at first. But over time, the count was able to establish himself and his household in the relevant social and political networks. The study presents the contacts of the imperial diplomat to the opposition, his acceptance into the Royal Society as well as the freemasons, and the use of his position and standing in London society especially during the War of the War of the Polish Succession (1733–1735).